Phân tích thành nhân tử (2x2-3x-1)2-3(2x2-3x-5)-16
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a,=\left(x+1\right)\left(x+3\right)\\ b,=-5x^2+15x+x-3=\left(x-3\right)\left(1-5x\right)\\ c,=2x^2+2x+5x+5=\left(2x+5\right)\left(x+1\right)\\ d,=2x^2-2x+5x-5=\left(x-1\right)\left(2x+5\right)\\ e,=x^3+x^2-4x^2-4x+x+1=\left(x+1\right)\left(x^2-4x+1\right)\\ f,=x^2+x-5x-5=\left(x+1\right)\left(x-5\right)\)
2 x 2 + 3 x + 5 = 2 x 2 - 2 x + 5 x - 5 = 2 x 2 - 2 x + 5 x - 5 = 2 x x - 1 + 5 x - 1 = x - 1 2 x + 5
1: \(-x^2+2x+8\)
\(=-\left(x^2-2x-8\right)\)
\(=-\left(x-4\right)\left(x+2\right)\)
2: \(2x^2-3x+1=\left(x-1\right)\left(2x-1\right)\)
b) \(16x-5x^2-3=5x\left(3-x\right)-\left(3-x\right)=\left(3-x\right)\left(5x-1\right)\)
c) \(2x^2+3x-5=2x\left(x-1\right)+5\left(x-1\right)=\left(x-1\right)\left(2x+5\right)\)
d) \(2x^2+3x-5=2x\left(x-1\right)+5\left(x-1\right)=\left(x-1\right)\left(2x+5\right)\)
Bài 1:
a: \(=6x^3-10x^2+6x\)
b: \(=-2x^3-10x^2-6x\)
Bài 4:
a: =>3x+10-2x=0
=>x=-10
c: =>3x2-3x2+6x=36
=>6x=36
hay x=6
Bài 1:
\(a,=6x^3-10x^2+6x\\ b,=-2x^3-10x^2-6x\)
Bài 4:
\(a,\Leftrightarrow3x+10-2x=0\Leftrightarrow x=-10\\ b,\Leftrightarrow x\left(2x^2+9x-5\right)-\left(2x^3+9x^2+x+4,5\right)=3,5\\ \Leftrightarrow2x^3+9x^2-5x-2x^3-9x^2-x-4,5=3,5\\ \Leftrightarrow-6x=8\Leftrightarrow x=-\dfrac{4}{3}\\ c,\Leftrightarrow3x^2-3x^2+6x=36\Leftrightarrow x=6\)
Bài 1:
\(a,=7xy\left(2x-3y+4xy\right)\\ b,=x\left(x+y\right)-5\left(x+y\right)=\left(x-5\right)\left(x+y\right)\\ c,=\left(x-y\right)\left(10x+8\right)=2\left(5x+4\right)\left(x-y\right)\\ d,=\left(3x+1-x-1\right)\left(3x+1+x+1\right)\\ =2x\left(4x+2\right)=4x\left(2x+1\right)\\ e,=5\left[\left(x-y\right)^2-4z^2\right]=5\left(x-y-2z\right)\left(x-y+2z\right)\\ f,=x^2+8x-x-8=\left(x+8\right)\left(x-1\right)\\ g,\left(x+y\right)^3-\left(x+y\right)=\left(x+y\right)\left[\left(x+y\right)^2-1\right]\\ =\left(x+y\right)\left(x+y-1\right)\left(x+y+1\right)\\ h,=x^2+3x+x+3=\left(x+3\right)\left(x+1\right)\)
\(2x^2\left(x+1\right)+4\left(x+1\right)=2\left(x+1\right)\left(x^2+2\right)\)
\(-3x-6xy-9xz=-3x\left(1+2y+3z\right)\)
\(2x^2y-4xy^2+6xy=2xy\left(x-2y+3\right)\)
\(4x^3y^2-8x^3y^2+2x^4y=-4x^3y^2+2x^4y=2x^3y\left(x-2y\right)\)
1) \(2x^2\left(x+1\right)+4\left(x+1\right)=2\left(x+1\right)\left(x^2+2\right)\)
2) \(-3x-6xy-9xz=-3x\left(1+2y+3z\right)\)
3) \(2x^2y-4xy^2+6xy=2xy\left(x-2y+3\right)\)
4) \(4x^3y^2-8x^3y^2+2x^4y=-4x^3y^2+2x^4y=-2x^3y\left(2y-x\right)\)
\(\left(x-y\right)^2+4\left(x-y\right)+4\)
\(=\left(x-y\right)^2+2.\left(x-y\right).2+2^2\)
\(=\left(x-y+2\right)^2\)
hk tốt
^^
\(\left(x^2+4x+8\right)^2+3x\left(x^2+4x+8\right)+2x^2=\left(x^2+4x+8+\dfrac{3}{2}x\right)^2-\dfrac{1}{4}x^2=\left(x^2+\dfrac{11}{2}x+8\right)^2-\left(\dfrac{1}{2}x\right)^2=\left(x^2+\dfrac{11}{2}x+8-\dfrac{1}{2}x\right)\left(x^2+\dfrac{11}{2}x+8+\dfrac{1}{2}x\right)=\left(x^2+5x+8\right)\left(x^2+6x+8\right)=\left(x+2\right)\left(x+4\right)\left(x^2+5x+8\right)\)
\(\left(x^2+4x+8\right)^2+3x\left(x^2+4x+8\right)+2x^2\)
\(=\left(x^2+4x+8\right)^2+x\left(x^2+4x+8\right)+2x\left(x^2+4x+8\right)+2x^2\)
\(=\left(x^2+4x+8\right)\left(x^2+5x+8\right)+2x\left(x^2+5x+8\right)\)
\(=\left(x^2+5x+8\right)\left(x+2\right)\left(x+4\right)\)
b, (\(x^2\) - \(xy\) ) + (\(x-y\))
= (\(x-y\)).\(x\) + (\(x-y\))
= (\(x-y\)).(\(x\) + 1)
c, \(x^2\) - 2\(x\) - 15
= (\(x^2\) - 2\(x\) + 1) - 16
= (\(x\) - 1)2 - 42
= (\(x-1-4\)).(\(x-1+4\))
= (\(x-5\)).(\(x+3\))
a) (x - y)(x + y + 3). b) (x + y - 2xy)(2 + y + 2xy).
c) x 2 (x + l)( x 3 - x 2 + 2). d) (x – 1 - y)[ ( x - 1 ) 2 + ( x - 1 ) y + y 2 ].
\(=\left(2x^2-3x-1\right)^2-3\left(2x^2-3x-1-4\right)-16\)
\(=\left(2x^2-3x-1\right)^2-3\left(2x^2-3x-1\right)-4\)
\(=\left(2x^2-3x-1-4\right)\left(2x^2-3x-1+1\right)\)
\(=\left(2x^2-3x\right)\left(2x^2-3x-5\right)\)
\(=x\left(2x-3\right)\left(2x^2-5x+2x-5\right)\)
\(=x\left(2x-3\right)\left(2x-5\right)\left(x+1\right)\)